Estudios de prefactibilidad para el montaje de una empresa de servicios de alquiler de helicópteros para ejecutivos en Colombia (2014)
The development of an entrepreneurial project requires a high level of detail so that the results, linked to their proper development, are as expected. In the present work of degree the prefeasibility study of the assembly of a company of rent of helicopters for executives is developed, that in addition to being a project of emprendimiento, by its characteristics, requires of a methodology of integral development, that takes into account all the multiple needs and opportunities that point to the increase of the productivity, optimization of times and increase of security in the transport that demands the productive sector at present. The development of this project was realized from three main fronts; as a first instance, the strategic alignment of the project with the country's objectives, followed by a formulation phase that includes market, technical, environmental, administrative and financial studies, and finally a financial evaluation stage in which the financial results of the project are presented. the alternatives selected in the preceding studies.